2010
DOI: 10.1371/journal.pone.0012038
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 1α Determines Gastric Cancer Chemosensitivity via Modulation of p53 and NF-κB

Abstract: BackgroundReduced chemosensitivity of solid cancer cells represents a pivotal obstacle in clinical oncology. Hence, the molecular characterization of pathways regulating chemosensitivity is a central prerequisite to improve cancer therapy. The hypoxia-inducible factor HIF-1α has been linked to chemosensitivity while the underlying molecular mechanisms remain largely elusive. Therefore, we comprehensively analysed HIF-1α's role in determining chemosensitivity focussing on responsible molecular pathways.Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 49 publications
5
113
0
Order By: Relevance
“…82 ). Inhibition of the phosphoinositol-3-kinase (PI3K) pathway, nuclear factor kappa-B (NF-κB), cycloxygenase-2 (COX-2), activator protein-1 (AP-1), cjun, Pim-1, and STAT-3 can reverse resistance to cytostatics in hypoxia, implying a role for these pathways in hypoxia-induced drug resistance 10,18,22,23,33,77,83,84 . However, the degree in which they are dependent on functional HIF-1 is uncertain.…”
Section: Other Factors Responsible For Hypoxia-induced Chemoresistancementioning
confidence: 99%
“…82 ). Inhibition of the phosphoinositol-3-kinase (PI3K) pathway, nuclear factor kappa-B (NF-κB), cycloxygenase-2 (COX-2), activator protein-1 (AP-1), cjun, Pim-1, and STAT-3 can reverse resistance to cytostatics in hypoxia, implying a role for these pathways in hypoxia-induced drug resistance 10,18,22,23,33,77,83,84 . However, the degree in which they are dependent on functional HIF-1 is uncertain.…”
Section: Other Factors Responsible For Hypoxia-induced Chemoresistancementioning
confidence: 99%
“…The a-subunits, HIF-1a and HIF-2a, are degraded by the proteasome system in an oxygen-dependent manner [15]. HIF-1a has been reported to contribute to the chemoresistance of a wide range of solid tumors, including gastric cancer [16,17]. We reported that antisense HIF-1a therapy enhances the efficacy of doxorubicin in the treatment of hepatocellular carcinoma [18], and prevents acquired resistance to anti-angiogenic therapy in lymphomas [19].…”
mentioning
confidence: 92%
“…The molecular nature of this phenomenon was mostly explained by HIF1α anti-apoptotic target gene-induction (Bak, Bax, Bcl-xL, Bcl-2, Bid, Mcl-1, NF-κB, p53 and survivin), but also by suppression of p53 activation in response to chemotherapeutic agents [71], as it can be seen in Figure 3. HIF2α was recently shown to act in a similar manner, namely suppressing p53 activation and apoptosis in response to radiation-induced DNA damage in clear cell kidney cancer cells [69].…”
Section: Hifs and Cell Death Pathways: Apoptosis And Autophagymentioning
confidence: 99%